Synthesis and cellular bioactivities of novel isoxazole derivatives incorporating an arylpiperazine moiety as anticancer agents - Burcu Çalışkan; Esra Sinoplu; Kübra İbiş; Ece Akhan Güzelcan; Rengül Çetin Atalay; Erden Banoglu (Taylor & Francis Group, 2018)
In our endeavour towards the development of effective anticancer therapeutics, a novel series of isoxazole-piperazine hybrids were synthesized and evaluated for their cytotoxic activities against human liver (Huh7 and Mahlavu) and breast (MCF-7) cancer cell lines. Within series, compounds 5l-o showed the most potent cytotoxicity on all cell lines with IC50 values in the range of 0.3-3.7 μM. To explore the mechanistic aspects fundamental to the observed activity, further biological studies with 5m and 5o in liver cancer cells were carried out. We have demonstrated that 5m and 5o induce oxidative stress in PTEN adequate Huh7 and PTEN deficient Mahlavu human liver cancer cells leading to apoptosis and cell cycle arrest at different phases. Further analysis of the proteins involved in apoptosis and cell cycle revealed that 5m and 5o caused an inhibition of cell survival pathway through Akt hyperphosphorylation and apoptosis and cell cycle arrest through p53 protein activation.